Interaction between the Government and Society as a Factor of Social Solidarity in the Context of External Military and Political Aggression: Political and Psychological Aspects - Palahnyuk, Olha (My University, 2025)
ocial solidarity becomes particularly relevant, since stability, mobilization capacity, and resilience of society largely depend on it. The growing role of civil society, volunteer movements, and state communication policy highlights the need for a theoretical understanding of the mechanisms of solidarity. The aim of the study is to analyze the impact of interaction between the authorities and society on social solidarity in the context of external threats. The methodological basis is an interdisciplinary combination of content analysis, comparative analysis of international experience, and systematization of theoretical approaches in political psychology. The study reveals that emotional trust, social identifi cation, perceptions of justice, and citizens’ involvement in socially signifi cant practices play a key role in maintaining solidarity. The importance of symmetrical interaction between civic initiatives and state institutions as a condition for sustainable solidarity is substantiated. A typology of psychological barriers to solidarity and possible mechanisms for overcoming them is proposed. International experience of solidarity in crisis situations is summarized and elements relevant to the Ukrainian context are identifi ed. The practical signifi cance of the study lies in the formulation of recommendations for state communication policy, support for volunteer initiatives, the development of indicators of emotional inclusion, and the construction of long-term strategies for social unity
Keywords: social solidarity; social cohesion; civic engagement; political communication; crisis solidarity; political and psychological factors; public administration